Polysaccharides as a Green and Sustainable Resources for Water and Wastewater Treatment - Oladoja, Nurudeen A.; Unuabonah, Emmanuel I.; AMUDA, OMOTAYO S.; Kolawole, Olatunji M. (SpringerBriefs in Molecular Science,, 2017)
This brief critically reviews the structure and applications of polysaccharide based materials as a green and sustainable resource in water and water treatment operations. The authors present a fascinating insight into the application of this renewable resource in water and wastewater treatment operations approached from multiple perspectives: mechanistic insight into the coagulation efficiency of polysaccharides based coagulants; progress and prospects of polysaccharide composites as adsorbent for water and wastewater treatment; structural modifications of polysaccharides for enhanced performance as adsorbents; tuning polysaccharides framework for optimal coagulation efficiency; and tapping into microbial polysaccharides for water and wastewater purifications. This brief is aimed at professionals active in the science and engineering aspects of water and wastewater treatment operations. .